DEVELOPING A PROJECT BASED LEARNING MODEL INCORPORATING PRIOR KNOWLEDGE ACTIVATION FOR TEACHING WRITING - Hoesny, Mariana Ulfah; Safitri, Isnaini Nur; Asri, Atiqah Nurul; Roisatin, Umi Anis (Fakultas Keguruan Ilmu Pendidikan Universitas Ibn Khaldun Bogor, 2025)
This research is aimed at developing a project-based learning model incorporating prior knowledge activation for teaching writing. Teaching writing is challenging since the skill comprises linguistic and cognitive aspects. Writing is a process of pouring ideas into text which involve cognitive domain; therefore, a model for teaching writing needs to be tailored so that learners can learn writing and improve their skill. This study is a Design and Development research comprising 5 stages namely analysis, design, development, implementation and evaluation (ADDIE). Through analysis, questionnaires were distributed to second grade students of MAN 5 Jombang. Interviews were also conducted with 2 teachers who taught writing to explore needs and problems in teaching writing. Then, design and development of the model was conducted, followed by implementing the model in MAN 5 Jombang. The result of analysis showed that students preferred learning model that involve them actively. In addition, students also stated that learning to write required knowledge regarding topics and other aspect related to writing such as grammar, mechanic and vocabulary. The model developed in this study employed project-based learning incorporating with prior knowledge. Thus, students learned in a project atmosphere, while prior knowledge activation was integrated in each phase to help them retrieve past knowledge and improve their writing. The result of pre and post-test showed that the model successfully improved students’ writing score from 50,39 to 86,21. The questionnaires distributed in evaluation stage revealed that students enjoyed the atmosphere of project-based learning and felt they understood the material better. In conclusion, the model successfully fixed learning atmosphere and improved students’ writing skill.